Case report: Clinical management of freshwater stingray wounds using negative pressure therapy - Nattrodt, Janio J. M.; Bezerra-de-Freitas, Victória A.; Merval, Ana Paula S. S.; Filardi, Eloise T.; Cerni, Felipe A.; Dantas, Domingos S. M.; Lins, Alysson B. M.; Galan, Luis E. B.; Carbonell, Roberto C.; Pucca, Manuela B. (Frontiers in Medicine, 2025)
Stingray injuries represent a significant occupational hazard, particularly for fishermen, and are commonly caused by freshwater stingrays of the Potamotrygonidae family. These stingrays are equipped with a sharp, bilaterally serrated spine that delivers venom, inducing vasoconstriction, severe pain, and ischemia. Such injuries are not only intensely painful but also debilitating, often rendering victims unable to work for weeks or even months. Traditional self-treatment practices, including the application of urine and herbal remedies, are widely relied upon in affected communities but are scientifically unproven and frequently lead to delayed or suboptimal care. This study presents two clinical cases of freshwater stingray envenomation from Roraima, the northernmost state of Brazil located within the Amazon Rainforest. Both cases were managed at the infectious disease unit of the General Hospital in Boa Vista, the state capital. Patients received evidence-based medical care, including intravenous antibiotic therapy and surgical debridement to remove necrotic and devitalized tissue. In one case, advanced negative pressure wound therapy (NPWT) was utilized during dressing changes, resulting in a clean wound devoid of edema and necrotic tissue, demonstrating the technique’s effectiveness in promoting wound healing. By accelerating wound healing and mitigating complications such as infections and chronic wounds, NPWT significantly enhance patient outcomes. Furthermore, this study underscores the limitations of traditional remedies and advocates for the adoption of evidence-based interventions, particularly in regions like the Brazilian Amazon, where access to healthcare can be challenging.